Cerebral Blood Flow in Orthostatic Intolerance - Muhammad Shahzeb Khan; Amanda J. Miller; Arooba Ejaz; Jeroen Molinger; Parag Goyal; David B. MacLeod; Ashley Swavely; Elyse Wilson; Meghan Pergola; Harikrishna Tandri; Camille Frazier Mills; Satish R Raj; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Cerebral blood flow (CBF) is vital for delivering oxygen and nutrients to the brain. Many forms of orthostatic intolerance (OI) involve impaired regulation of CBF in the upright posture, which results in disabling symptoms that decrease quality of life. Because CBF is not easy to measure, rises in heart rate or drops in blood pressure are used as proxies for abnormal CBF. These result in diagnoses such as postural orthostatic tachycardia syndrome and orthostatic hypotension. However, in many other OI syndromes such as myalgic encephalomyelitis/chronic fatigue syndrome and long COVID, heart rate and blood pressure are frequently normal despite significant drops in CBF. This often leads to the incorrect conclusion that there is nothing hemodynamically abnormal in these patients and thus no explanation or treatment is needed. There is a need to measure CBF, as orthostatic hypoperfusion is the shared pathophysiology for all forms of OI. In this review, we examine the literature studying CBF dysfunction in various syndromes with OI and evaluate methods of measuring CBF including transcranial Doppler ultrasound, extracranial cerebral blood flow ultrasound, near infrared spectroscopy, and wearable devices.